2005
DOI: 10.1007/0-387-26206-7_29
|View full text |Cite
|
Sign up to set email alerts
|

Past, Present, and Future of Oxygen in Cancer Research

Abstract: The first pathologists, oncologists, and medical physicists were aware that tumors were populated by an aberrant vasculature. The classic observations of Thomlinson and Gray in the 1950's established that O2 diffusion distances caused tumor to grow in cords. Tumor necrosis was observed surrounding a Krogh cylinder of viable tumor. That work helped explain earlier work by Warburg, who demonstrated a predisposition for tumors to favor anaerobic respiration, and it became the basis for 5 decades of subsequent res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Even today, scientists lack an optimal method of direct tissue O 2 measurement that is noninvasive, precise, and quantitative; but this goal is clearly within reach (reviewed in 7 ). In the 1980's, in vivo polarographic measurements with electrodes and ex vivo cryospectrophotometric measurements of oxyhemoglobin provided some insight into the regional oxygenation status of tumors (reviewed in 8 ).…”
Section: Early Demonstrations Of Tumor Hypoxiamentioning
confidence: 99%
“…Even today, scientists lack an optimal method of direct tissue O 2 measurement that is noninvasive, precise, and quantitative; but this goal is clearly within reach (reviewed in 7 ). In the 1980's, in vivo polarographic measurements with electrodes and ex vivo cryospectrophotometric measurements of oxyhemoglobin provided some insight into the regional oxygenation status of tumors (reviewed in 8 ).…”
Section: Early Demonstrations Of Tumor Hypoxiamentioning
confidence: 99%
“…This can be understood in terms of cell biology: BC is promoted by the progressive accumulation of genetic and epigenetic changes in the breast cells [6], leading to cellular oxidative stress [7,8], and, thus, to the emission of BC-specific volatile biomarkers into the blood [9][10][11][12]. BC-promoting DNA methylation of certain genes has been observed even in benign lesions, indicating that epigenetic changes (very probably accompanied by measurable emission of volatile biomarkers) occur very early in the tumor genesis [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…The third case was characterized by cyclic periods of hypoxia and reoxygenation [Cooper et al, 2004;Weinmann et al, 2004Weinmann et al, , 2005Okunieff et al, 2005;Yao et al, 2005;Liu et al, 2006;Martinive et al, 2006;Dewhirst, 2007]. The previous studies showed that the major phenotypic shift associated with chronic hypoxia led to cellular resistance to chemotherapy, radiotherapy, promoting the tumor cells to become more invasive and metastatic.…”
mentioning
confidence: 95%